Learning from Power Sector Reform : The Case of the Arab Republic of Egypt - Rana, Anshul; Khanna, Ashish (World Bank, Washington, DC, 2020)
The challenge of power sector reform in the Arab Republic of Egypt has long been dominated by extremely high subsidies, with prices set well below the costs of supply. These subsidies have taken a variety of forms: explicit subsidies in the government budget, implicit subsidies in the underpricing of fuel supply (particularly natural gas) to the power sector, accumulation of arrears from the sector, poorly-maintained physical capital, and cross-subsidies across customer classes. Egypt's social contract was linked to expanding energy access with good quality supply based on public financing and huge subsidies. Egypt has been able to achieve universal access with more or less reliable power over the entire period, except when chronic underinvestment in the sector caused blackouts in 2011–14 at time of severe political uncertainty. The social compact came under pressure in 2014 when energy subsidies reached 6.8 percent of gross domestic product. Since then, the reform process has been revived based on new electricity, gas, and renewable energy laws; price and subsidy adjustments; structural reforms with a deliberately long time frame; and greater emphasis on the role of the private sector.